Neglected and Underutilized Crop Species: The Key to Improving Dietary Diversity and Fighting Hunger and Malnutrition in Asia and the Pacific - Li, Xuan; Yadav, Rashmi; Siddique, Kadambot H. M. (Frontiers in Nutrition, 2020)
Asia continues to suffer from a high prevalence of malnutrition. Low dietary diversity, coupled with low production diversity, is the leading cause of persistent malnutrition. Dietary diversity represents a more healthy, balanced, and diverse diet, which ensures nutrient adequacy. The principle of dietary diversity is affirmed in all national food-based dietary guidelines. Food-based approaches that address malnutrition, especially micronutrient deficiencies, are embedded in evidence-based healthy diet patterns; however, they are disconnected from the current agricultural production system. Promising neglected and underutilized species (NUS) that are nutrient-dense, climate-resilient, economically viable, and locally available or adaptable are the key to improving dietary and production diversity. The Future Smart Food Initiative, led by FAO's Regional Initiative on Zero Hunger, aims to harness the enormous benefits that NUS offer in the fight against hunger and malnutrition.